Perioperative pain management and outcomes in patients who discontinued or continued pre-existing buprenorphine therapy - Attaar, PharmD, BCPS, Aamer; Curran, PharmD, BCPS, BCCCP, Molly; Meyenburg, PharmD, BCPS, Lyndsi; Bottner, DHA, PA-C, Richard; Johnston, MD, Clarissa; Mason, PharmD, BCPS, Kirsten Roberts (Journal of Opioid Management, 2021)
Objective: This study compared opioid utilization and clinical outcomes in surgical patients receiving maintenance buprenorphine therapy who discontinued versus those who continued buprenorphine treatment perioperatively. Lack of high-quality evidence, conflicting results in previous studies, and the possible need for reinduction after discontinuing therapy present clinicians with the complicated dilemma of choosing the best strategy to control post-operative pain in patients receiving buprenorphine. Design: A multicenter, retrospective cohort study. Participants: Hospitalized patients between January 1, 2017 and December 12, 2019 who underwent any type of surgery, had a documentation of an outpatient buprenorphine prescription or inpatient order, and received buprenorphine for 5 or more days prior to the procedure were included. Main outcome measure(s): The primary objective was to compare mean 24-hour morphine milligram equivalent (MME) utilization post-operatively between patients who discontinued buprenorphine preoperatively versus those who continued therapy throughout the perioperative period. Results: Fifty-one patients met the inclusion criteria for this study. Of these, 42 patients were continued on buprenorphine through surgery, while nine patients had a documentation of discontinuation preoperatively. The 24-hour post-operative MME utilization (interquartile range) was 58.8 (18-100.8) in patients who continued therapy through surgery versus 152.6 (114.5-236) in patients who discontinued therapy preoperatively (p = 0.005). There were no significant differences in post-operative pain scores or length of stay between groups. Conclusion: Post-operative opioid use was significantly lower in patients who continued buprenorphine compared with those who discontinued buprenorphine preoperatively.